Factors influencing the implementation of cardiopulmonary resuscitation among college freshmen: Based on the Theory of Planned Behavior - Qinfei Wei; Yu Jiang; Xuemei Lin; Jun Feng; Shan Huang; Feng Wang; Li Fang; Yan Zhang (PLoS ONE, 2025)
Objective Cardiac arrest is a leading cause of global mortality, for which timely cardiopulmonary resuscitation (CPR) is a critical intervention. However, public competence in CPR remains low. Grounded in the Theory of Planned Behavior (TPB), this study investigated the factors influencing CPR implementation among college freshmen by examining their behavioral intention. Methods A cross-sectional study was conducted among college freshmen undergoing a basic entrance physical health screening at Fuzhou First General Hospital between September 2 and 9, 2024. Participants were randomly selected to complete an electronic questionnaire, which included a general information sheet and the validated Public Behavior Intention Scale for Performing CPR, adapted with input from emergency medicine experts. Statistical analyses included correlation, regression, and mediation analysis. Results Among 4,929 valid questionnaires analyzed, a higher willingness to perform CPR was associated with undergraduate enrollment, good personal and family health status, prior CPR performance, and no history of transient loss of consciousness. Multiple linear regression identified behavioral attitude (β = 0.439), subjective norm (β = 0.272), CPR knowledge (β = 0.027), and perceived behavioral control (β = 0.070) as significant predictors of CPR behavioral intention (all P < 0.01). Mediation analysis further revealed that CPR knowledge influenced behavioral intention primarily through its effects on behavioral attitude (79.43% of the total effect), subjective norm (61.31%), and perceived behavioral control (43.67%). Conclusion Behavioral attitude serves as the principal pathway through which CPR knowledge translates into intention to act. These findings underscore that targeted CPR training in universities should address both knowledge and psychosocial factors to strengthen students’ willingness to act.